2020
DOI: 10.1002/jsfa.10333
|View full text |Cite
|
Sign up to set email alerts
|

Consumer rejection threshold, acceptability rates, physicochemical properties, and shelf‐life of strawberry‐flavored yogurts with reductions of sugar

Abstract: BACKGROUND There is an increasing demand for reduced‐sugar products due to the worldwide prevalence of obesity, diabetes, and cardiovascular diseases. The aim of this study was to evaluate the effects of sugar (sucrose) reductions on the acceptability, preference, and quality of strawberry‐flavored yogurts. A consumer rejection threshold test and an acceptability test (N = 53) were conducted using six yogurt samples with decreasing concentrations of sugar (12–5/100 g). Additional physicochemical tests (pH, °Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Similar to the findings in the present study, Shourideh et al [33] found that a 100% tagatose dark chocolate sample had a similar apparent viscosity compared to the value of a 100% sucrose sample. Parallel to our results, the viscosity values decreased significantly for all the yogurt samples after 28 days of storage at 4 °C [23]. Stabilizers, such as polysaccharides or gelatin, can avoid the whey separation in yogurt products [34].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Similar to the findings in the present study, Shourideh et al [33] found that a 100% tagatose dark chocolate sample had a similar apparent viscosity compared to the value of a 100% sucrose sample. Parallel to our results, the viscosity values decreased significantly for all the yogurt samples after 28 days of storage at 4 °C [23]. Stabilizers, such as polysaccharides or gelatin, can avoid the whey separation in yogurt products [34].…”
Section: Discussionsupporting
confidence: 81%
“…Six sucrose/tagatose concentrations were prepared with equidistant decrements of sucrose (8.50, 6.80, 5.10, 3.40, 1.70, and 0.00 g/100 g of yogurt), and their respective equidistant increments of tagatose (0.0, 1.85, 3.70, 5.54, 7.39, and 9.24 g/100 g of yogurt) to determine the most accepted sucrose/tagatose concentration in the strawberry-flavored yogurts (Table 1). The 8.5%-sucrose concentration was selected as the starting point because it was the most preferred concentration of sucrose in strawberry-flavored yogurt from a preliminary study [23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found that a sugar reduction of 14% sucrose can be adopted without compromising sensory acceptability. Torrico, Tam, Fuentes, Viejo, and Dunshea (2020) managed to further reduce sugar in strawberry yogurt, showing that analysis of the consumer rejection limit allowed for reducing sucrose to less than half of the initial concentration without affecting consumer preferences. In other food categories, Pineli et al (2016) reported that sugar reductions could be up to 15% in nectar juice, while Oliveira et al (2016) identified a sugar reduction of up to 29% in chocolate milk without affecting sensory acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…In order to elucidate safe reduction levels for industry and the consumer, additional studies with yogurt and other food categories in different cultures are needed, because to date the consumer appears to be more tolerant to fat reduction in yogurt than to sugar reduction (Dias et al, 2020). For example, Torrico et al (2020) reported that the ideal level of sugar reduction in yogurt highly depends on the impact caused to its physicochemical properties, which in turn strongly interfere with preference and sensory acceptability.…”
Section: Discussionmentioning
confidence: 99%